If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5y-12)=(-5y-1)
We move all terms to the left:
(5y-12)-((-5y-1))=0
We get rid of parentheses
5y-((-5y-1))-12=0
We calculate terms in parentheses: -((-5y-1)), so:We get rid of parentheses
(-5y-1)
We get rid of parentheses
-5y-1
Back to the equation:
-(-5y-1)
5y+5y+1-12=0
We add all the numbers together, and all the variables
10y-11=0
We move all terms containing y to the left, all other terms to the right
10y=11
y=11/10
y=1+1/10
| y*y=y | | 4(2x+5)+5(4x+5)+6=28x+52 | | s+8=15 | | 2(w-3)-4=-4(-5w+4)-6w | | 1/3x-225=-125 | | 9j=13j-2 | | y-5=3-y(y+2) | | ((x+8)/x)=3 | | x/2+12=1/10 | | 5^x=72 | | -5x+47=-7(x-7) | | 4x+8=4(×+2) | | 3/x=18/72 | | 35-m=15 | | 4x(x-2)=(2x+3)(2x-5) | | 3(w+6)-5w=8 | | 7x-1+5x+7=112 | | X/3=1/3x | | 3(4d+1)-9d=6d(2-d) | | (n-2)180/n=72 | | 2^x+4-2^x=144 | | 2(5x+5)+2(5x+5)+4=20x+25 | | 3x5x=42 | | 2/3-5w=3w+2/15 | | 1x-9=8(2x+3)-18 | | 7q=70 | | 12x+6=21x-35 | | 9^-2y=12 | | (2m+1)^2m=7 | | -2x+15=41 | | -14.4=u/7-3.2 | | 7n+2-3n+2=3(3n-7) |